EFFECT OF CADMIUM CHLORIDE ON THE SPERMATOGENESIS OF MUSCA DOMESTICA NEBULO F. (DIPTERA : MUSCIDAE) - SAIN, MALKIAT. S.; GILL, JAGIT K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1985)
Various concentrations of Cadmium chloride ranging from 0.01 to 5.00% were given with food as a chemosterilant to the house fly, Musca domestica, Concentrations of 0.01 to 0.09% affect only the general health of the individual but there occurs no sterility. Concentrations ranging from 0.1 to 2.0% cause a temporary but complete sterility. The higher doses of 3.00 to 4.00% concentrations induce permanent complete sterility. With 5.00% concentration, there is either no emergence of adult flies or, if any they die after few hours of emergence.